Maternal Stress and Coping Strategies in Developmental Dyslexia: An Italian Multicenter Study - Carotenuto, Marco; Messina, Antonietta; Monda, Vincenzo; Precenzano, Francesco; Iacono, Diego; Verrotti, Alberto; Piccorossi, Alessandra; Gallai, Beatrice; Roccella, Michele; Parisi, Lucia; Maltese, Agata; Lavano, Francesco; et al. (Frontiers in Psychiatry, 2017)
Background: Studies about the impact of developmental dyslexia(DD) on parenting arerare. Our investigation aimed to assess maternal stress levels and mothers’ copying styles in a population of dyslexic children. Methods: A total of 874 children (500 boys, 374 girls;(mean age 8.32±2.33 years) affected by DD was included in the study. A total of 1421 typically developing children (789 boys, 632 girls; mean age 8.25±3.19 years)were recruited from local schools of participating Italian Regions (Abruzzi, Calabria, Campania, Puglia, Umbria, Sicily) and used as control-children group.All mothers (of bothDD and typically developing children) filled out an evaluation for parental stress (Parenting Stress Index- Short Form: PSI-SF) and coping strategies (Coping Inventory for Stressful Situations:CISS). Results: No statistical differences for mean age (p=0.456) and gender (p=0.577) were found between DD and control children. Mothers of children affected by DD showed an higher rate of all parental stress indexes (Parental Distress domain p<0.001; Difficult Child p<0.001; Parent-Child Dysfunctional Interaction p<0.001; and Total Stress subscale score p<0.001) than controls mothers. According to the CISS evaluation, mothers of DD children reported a significantly higher rate of emotion-oriented (p<0.001) and avoidance-oriented (p<0.001) coping styles than mothers of typical developing children. On the other hand, a lower representation of task-oriented coping style was found in mothers of DD children (p<0.001) in comparisonto mothers of control-children. Conclusions: Our study shows the clinical relevance of the burden carried by the mothers of children affected by DD and suggests the importance to assess parents, particularly mothers, to improve family compliance and clinical management of this disorder.